PENYULUHAN KESEHATAN TENTANG PENGETAHUAN MENGENAI VAGINAL DISCHARGE PADA REMAJA PUTRI DI SMA NEGERI 01 DARUL KAMAL ACEH BESAR - Raudhatun Nuzul ZA; Rahmayani . (JURNAL PENGABDIAN KEPADA MASYARAKAT BIDANG KESEHATAN, 2020)
In Indonesia, about 90% of women have the potential to experience vaginal discharge because Indonesia is a tropical area so that the fungus is easy to develop which results in many cases of vaginal discharge. Symptoms of vaginal discharge are also experienced by unmarried women or girls aged 15-24 years, which is around 31.8%. This shows that adolescents are more at risk of developing vaginal discharge. In 2002 as many as 50% of Indonesian women had experienced vaginal discharge, then in 2003 it increased to 60% and in 2004 it increased again to almost 70% of Indonesian women who had experienced vaginal discharge at least once in their life. Adolescence is the most complex phase of development with all its problems. The most important phase for adolescents is puberty, where for young women is marked by the maturity of the reproductive organs. Leucorrhoea (leukorrhea, white discharge, or fluoralbus) is a symptom in the form of discharge from the genital organs that is not in the form of blood. This discharge is a physiological condition from the female genital tract. The entire surface of the female genital tract can discharge in the form of a saturated mucus, colorless and odorless.